Peran Umkm (Usaha Mikro, Kecil, Dan Menengah) Terhadap Pertumbuhan Perekonomian Indonesia - Fawwazky Raja Putra Kiswandi; Muhamad Cesario Setiawan; Muhammad Alif Ghifari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Micro, small and medium-sized enterprises (MSMEs) are an important part of maintaining a healthy and sustainable growth momentum. An objective evaluation of MSMEs' contribution to the economy can help generate better policies to optimize their potential. This research uses descriptive and qualitative data analysis, as well as a literature review. MSMEs have several advantages that can make them central in future business development. These advantages include: (a) MSMEs provide opportunities and employment that can be absorbed by up to 50% of the available workforce. (b) The existence of MSMEs can create and stimulate the growth and development of new entrepreneurs. (c) MSMEs have unique market segments and can easily manage changes that may occur in the market. (d) Because of their ability to utilize natural resources, MSMEs can utilize most of the products produced by large industries or other industries. (e) MSMEs have great potential for development. In addition, Micro, Small, and Medium Enterprises (MSMEs) offer benefits to the Indonesian economy by absorbing labor and impacting the country's GDP every year. This shows the potential of MSMEs in helping Indonesia achieve a sustainable economy.